Asymmetric Information in Nempil Ayam Transactions in Traditional Markets: A Sharia Economic Law and Consumer Protection Perspective - Nur Lailah; Galuh Widitya Qomaro; Mohammad Ali Hisyam; Ahmad Musadad (Fakultas Syariah IAIN Langsa, 2026)
The practice of nempil chicken transactions in traditional markets should ideally be conducted based on the principles of justice, openness, transparency, and mutual consent, as emphasized in Islamic economic law and Law Number 8 of 1999 on Consumer Protection. In reality, however, asymmetric information remains prevalent, particularly regarding access to information about chicken prices and quality, placing consumers in a disadvantaged position in transactions. This study aims to analyze the practice of nempil chicken transactions from the perspectives of Islamic economic law and consumer protection, as well as to identify forms of information asymmetry occurring in such transactions. The study employs a qualitative method with a descriptive-analytical approach through observations and interviews conducted in several traditional markets in Surabaya. The findings reveal differences in prices offered to ordinary consumers and fellow traders, as well as limited consumer access to information concerning chicken prices and quality, potentially involving elements of gharar and tadlis. This study contributes to the development of a consumer protection model based on Islamic economic law by strengthening price transparency, educating traders and consumers, and enhancing market supervision to promote nempil transactions that are fairer, more transparent, and consistent with Islamic principles.